PERSEPSI KONSUMEN DALAM MEMILIH KAMERA DIGITAL MENGGUNAKAN METODE TAM - Abdurahman Fauzi; Asep Ririh Riswaya (Jurnal Computech & Bisnis (e-Journal), 2019)
The purpose of this study to determine the perception of consumers in choosing a digital camera. The results of the research in Store CAMZONE Bandung is the value obtained as a material evaluation of academic materials on campus. The low interest in buying consumers because many not understand in choosing, for solving the problem the author using Technologi Acceptance Model (TAM) method that is suitable to test the problem. The author uses three constructs: perception of perceived usefulness (perceived ease of use), attitude towards using, to test cosnumeners. This study draws a sample population of 100 from 745 people, sampling technique using random sampling, data collection using questionnaires, testing using multiple linear regression analysis. The result of the influence of Perceived Usefulness (X1) and Perceived Ease Of Use (X2) together with Attitude Toward Using (Y) is 14.6% and the rest 85.4% is influence by other variables outside this research. Keywords: Consumer Influence, Digital Camera, Technology Acceptance Model (TAM), Multiple Linear Regression AnalysisDOI : http://doi.org/10.5281/zenodo.3625317